Basics in cheminformatics: representation of chemical structures 2 - Engel, Thomas (Henry Stewart Talks, 2024)
Stereochemistry, SMILES (Simplified Molecular Input Line Entry Specification), Sybyl linear notation, SLN syntax, IUPAC International Chemical Identifier, InChi and InChiKey, Morgan algorithm, Visualization of molecular models, Molecular surfaces